Evaluation of BioThrax® and AV7909 anthrax vaccines in adults 66 years of age or older - Wolfe, Daniel N.; Espeland, Eric M.; Gao, Yonghong; Lu, Di; Blatner, Gretta; Amass, Kathryn; Horwith, Gary; Tong, Xiaomi M.; Hopkins, Robert; David, Gloria L.; Jepson, Brett M.; King, James C. (Vaccine, 2020)
Multiple Anthrax vaccines are licensed or in development for post-exposure prophylaxis in individuals 18 to 65 years of age. No information exists on anthrax vaccines in populations over the age of 65. It is critical that we assess the capacity of anthrax vaccines to generate a protective immune response in older individuals. In this study, we compared BioThrax® to a formulation containing a CpG adjuvant (AV7909). We conducted a Phase 2 clinical study to evaluate safety and immunogenicity of three vaccination schedules of the AV7909 vaccine candidate and one vaccination schedule of BioThrax® vaccine in adults over 65 years of age. A total of 305 subjects were enrolled to assess safety and immunogenicity by seroprotection rates, toxin neutralizing antibody titers, and anti-Protective Antigen ELISA titers. Compared to BioThrax, AV7909 elicited a more robust immune response in older subjects, especially with three doses of AV7909 at Days 1, 15, and 29, or two doses at Days 1 and 29. These trends were true with both seroprotection rates as defined by the percentage of subjects with 50 percent neutralization factors greater than 0.56, and geometric mean antibody titers. The responses to both AV7909 and BioThax were lower in older subjects compared to those aged 18–50. The immunogenicity data suggest that the CpG adjuvant in the AV7909 vaccine helps to elicit a more robust immune response in subjects over the age of 65. Alternative dosing strategies may be considered in this population given the high seroprotection rates with Day 1 and 29, or Day 1, 15, and 29 regimens. Trial Registration: clinicaltrials.gov Identifier: NCT03518125.